The history and evolution of tourism - Christou, Prokopis A. 1978- (CABI, 2022)
"This book provides an overview of the history and evolution of tourism to the present, and speculates on possible and probable change into the future. It uses several practitioner-linked, real-life examples and case studies derived from all aspects of the tourism, travel and events industries"--